Investigation of photo-bleaching through transmittance method in pigmented solution: Understanding possible mechanisms and advantages for photo dental whitening - Florez, F. L E; Lins, E. C C C; Portero, P. [UNESP]; Lizarelli, R. F Z; Oliveira, O. B. [UNESP]; Bagnato, V S (SPIE, the international society for optics and photonics, 2007)
The dental bleaching is known for many years. Recently a technique employing light has open up new and exciting possibilities. Besides its vast application there are still many important points to be understood about teeth photon bleaching. In this work we present an in vitro experiment to explore the main mechanisms involved during the photon action in tooth whitening. Our results indicated that light at same wavelengths are great absorbed by pigments creating a local heating which considerably increase the bleaching rate. This results in a fast reaction without heating the whole dental structure. We discuss details of our experiment. Work supported by Fapesp and CNPq.
Keywords: Bleaching; Light absorption; Photons; Pigments; Dental bleaching; Dental structure; Photon bleaching; Dentistry